PEMBERDAYAAN PEREMPUAN DALAM MENDUKUNG USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) DI INDONESIA - Marthalina Marthalina (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2018)
The existence of gender equality in Indonesia has provided new hope for women to be involved and make decisions in the businesses they pursue. At present, women have acted as partners of husbands in meeting family needs and actively participating in social life, government organizations or local organizations. Working women have contributed to improving the welfare of the family economy in meeting the needs for clothing, food and shelter. Unfortunately the pace of gender equality in Indonesia is still constrained by the low confidence of banks to provide capital loans, which is only around 45% -55%. Women’s empowerment in the UMKM sector is expected to reduce poverty, provide increased income, increase knowledge and quality of human resources and prepare women’s communities to become a community that is friendly to banks and the economy. This reseach uses qualitative data analysis with data sources in the research obtained from the literature study documents relating to the empowerment of women and micro, small and medium enterprises. The documents in this study can be in the form of regulations, books and news sources from the internet. The data analysis was carried out descriptively by reducing data, presenting data and making conclusions. It was concluded that women’s empowerment in supporting UMKM in Indonesia had enormous potential and had to be optimized by the central government and regional governments. Cooperation is needed from various private parties, banks and other institutions in supporting women’s empowerment. A place is needed to accommodate women workers to be more able to play a role in the business sector, the need for training in entrepreneurship training, product innovation, management to improve women’s skills in the field of entrepreneurship so that productive activities have the value of education and high competitiveness. Keywords: role of women, entrepreneurship